2017
DOI: 10.1039/c6fo01535b
|View full text |Cite
|
Sign up to set email alerts
|

Formononetin inhibits human bladder cancer cell proliferation and invasiveness via regulation of miR-21 and PTEN

Abstract: The isoflavone formononetin is the main active component of Astragalus membranaceus and possesses anti-tumorigenic properties. However, the role of formononetin in human bladder cancer (BCa) has not been fully elucidated. The aim of the present study was to investigate the anti-tumor effects of formononetin on BCa cells and its potential molecular mechanism. T24 cells were treated with different concentrations of formononetin, and then the cell proliferation was assessed by MTT assay, cell apoptosis by Hoechst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…But the effects of miR-21-5p on malignant cellular phenotypes of BC are not very clear. Wu Y reported that formononetin could inhibit the invasiveness of BC cells and decrease the expression of miR-21 20 , but the correlation of miR-21-5p expression and the growth and metastasis of BC was not certain.…”
Section: Introductionmentioning
confidence: 99%
“…But the effects of miR-21-5p on malignant cellular phenotypes of BC are not very clear. Wu Y reported that formononetin could inhibit the invasiveness of BC cells and decrease the expression of miR-21 20 , but the correlation of miR-21-5p expression and the growth and metastasis of BC was not certain.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the major biologically active compounds in a variety of Chinese medicinal herbs, such as astragalus, which has been traditionally used for treatment of diabetes over 2000 years in China. Current research evidences indicated that formononetin played several different effects, such as, anti-inflammatory [ 6 , 7 ], antioxidative [ 8 ], antitumor [ 9 ], and promoting apoptosis [ 10 ]. Lima Cavendish et al confirmed that formononetin has an anti-inflammatory effect on rats with peritonitis [ 6 ] and could protect mice from lipopolysaccharide-induced acute lung injury [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As stated in Section 2.1.8 , miR-21 directly modulates PTEN, whose function is to inactivate PI3K/Akt signaling in cancer. As a consequence of the miR-21 inhibition, formononetin and galangin upregulate PTEN levels in bladder and cholangiocarcinoma, respectively, thereby inhibiting cancer aggressiveness [ 42 , 43 ]. In colorectal cancer, gambogic acid induces apoptosis by suppressing miR-21 expression, and the cytotoxicity of gambogic acid is reversed by overexpressing miR-21 [ 44 ].…”
Section: Oncogenic Mirnas Inhibited By Phytochemicals Currently Evmentioning
confidence: 99%